2020
DOI: 10.1038/s41612-020-00144-9
|View full text |Cite|
|
Sign up to set email alerts
|

Historical predictability of rainfall erosivity: a reconstruction for monitoring extremes over Northern Italy (1500–2019)

Abstract: Erosive storms constitute a major natural hazard. They are frequently a source of erosional processes impacting the natural landscape with considerable economic consequences. Understanding the aggressiveness of storms (or rainfall erosivity) is essential for the awareness of environmental hazards as well as for knowledge of how to potentially control them. Reconstructing historical changes in rainfall erosivity is challenging as it requires continuous time-series of short-term rainfall events. Here, we present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…Acquaotta et al (2019) also confirmed an upward erosivity trend for the period 1981-2015 in much of northern Italy. This increasing trend, together with increased inter-annual variability, is in fact a continuous process of precipitation intensification in Northern Italy, which began in the 1700s, likely associated with an increase in the frequency of extreme short-term rainfall events (Diodato et al 2020b). This means that northern Italy has been exposed to a progressively increasing inter-annual variability in rainfall erosivity, resulting in an increased hazardous landscape stress.…”
Section: Regional Change Perspective On Rainfall Erosivitymentioning
confidence: 98%
See 1 more Smart Citation
“…Acquaotta et al (2019) also confirmed an upward erosivity trend for the period 1981-2015 in much of northern Italy. This increasing trend, together with increased inter-annual variability, is in fact a continuous process of precipitation intensification in Northern Italy, which began in the 1700s, likely associated with an increase in the frequency of extreme short-term rainfall events (Diodato et al 2020b). This means that northern Italy has been exposed to a progressively increasing inter-annual variability in rainfall erosivity, resulting in an increased hazardous landscape stress.…”
Section: Regional Change Perspective On Rainfall Erosivitymentioning
confidence: 98%
“…Long-term reconstructions of rainfall erosivity can help to disentangle the role of anthropogenic climate change and the natural variability of the climate system in heavy rainfall events and floods (Diodato et al 2020a(Diodato et al , 2020b. The latter, through atmospheric-oceanic teleconnection patterns such as El Niño Southern Oscillation (ENSO), the North Atlantic Oscillation (NAO), the Atlantic Multidecadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO), can drive the frequency and intensity of regional rainfall events worldwide (Wetter et al 2011, Willems 2013, Gómara et al 2018, Diakhaté et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 d, black squared). Recently published studies on the relationship between hydrological extremes and climate change 34 , including rainfall erosivity 35 37 , indicate a new focus of environmental science about the history of extreme hydroclimatic events. Indeed, there are studies regarding the relationship between erosive forcing and climate in the central Mediterranean region 38 44 , indicating renewed attention to environment–climate interactions in historical and ecological research in support of reconstruction of extreme rainfall events (including rainfall erosivity) and planning decisions, especially in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, modelling rainfall erosivity requires exploring mechanisms inherited from past hydrological extremes like storms and floods 45 , using parsimonious models to overcome the limitations imposed by detailed models, which required detailed data and cannot be applied to historical periods 46 . In particular, low-resolution historical documentary records of extreme weather events can be adopted to help predict rainfall erosivity when satisfactory instrumental data are not available 37 . However, the floods of the Roman period, and earlier times, are almost all dated on an annual time-scale.…”
Section: Introductionmentioning
confidence: 99%
“…Damaging hydrological events triggered by either short and intense storms, or longer duration rainfall (e.g., Diodato et al, 2020b;Duulatov et al, 2021), cause sustained erosive forcing and considerable soil losses in many parts of the world (Wuepper et al, 2020). They may increase in frequency and/or severity with changes in the climate system associated with global warming (Easterling et al, 2000;Morera et al, 2017;Harris et al, 2018;Rineau et al, 2019;Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%